The context of the informant narrative performance from sociolinguistics to ethnolinguistics at Fort Chipewyan, Alberta - Scollon, Ronald 1939-2009 (Nat. Museums of Canada, 1979)
Demonstration how narrative structure at Fort Chipewyan, Alberta in highly sensitive to the situation of the narrative performance.
Keywords: Chipewyan; Chippewyan (Langue); Contexteffecten; Ethnolinguistique; Langues indiennes d'Amérique - Alberta; Sociolinguistique; Verteltheorie; Chipewyan Indians; Communication in folklore -- Alberta -- Fort Chipewyan; Discourse analysis, Narrative; Folklore -- Alberta -- Fort Chipewyan -- Performance; Languages in contact -- Alberta -- Fort Chipewyan; Oral tradition -- Alberta -- Fort Chipewyan; Protoalgonkianisch; Wörterbuch; Englisch